Edukasi Pencegahan Judi Online dan Pinjaman Online Ilegal Melalui Kunjungan Edukatif Ke Otoritas Jasa Keuangan - Akhmad Sayuti; Amelia Anggraini; Novita Sari; Nurlista Iryanti; Nyimas Maynisa Aulia (Jurnal Ilmu Sosial Terapan, 2026)
The development of digital technology provides convenience in people's financial activities, but also poses various risks such as the rise of online gambling and illegal online loans. Low financial literacy causes people, especially the younger generation, to be vulnerable to being entangled in illegal financial activities that have an impact on social and economic conditions. This Community Service (PKM) activity aims to increase participants' understanding and awareness of the dangers of online gambling and illegal online loans through educational visits to the Financial Services Authority. The implementation method is carried out through socialization activities, delivery of educational materials, interactive discussions, and direct observation related to the functions and roles of the OJK in supervising the financial services sector. Participants in the activity consisted of students who were given an understanding of the characteristics of legal and illegal online loans, the negative impact of online gambling, and measures to prevent illegal financial activities. The results of the activity showed an increase in participants' knowledge and awareness of the importance of digital financial literacy and awareness of various technology-based financial crime modes. The increase in participants' knowledge was divided into 3 evaluations, namely understanding of online gambling, online gambling and OJK Literacy, resulting in a significant percentage increase, namely for online gambling before activities at 45% after activities increased to 85%, for online loans before activities at 50% after activities increased by 90% and finally OJK literacy before activities increased by 40% after activities to 88%. This activity is expected to form wiser financial behavior, improve participants' ability to make safe financial decisions, and be a preventive effort in suppressing the spread of online gambling and illegal online loans in the community.